PENINGKATAN KINERJA CV. BUDII JAYA DIPENGARUHI OLEH KOMPETENSI DAN DISIPLIN KERJA - Sugiarti, Diyah; Swasti, Ika Korika (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Decreased employee performance that hinders the achievement of work targets is often influenced by competence and work discipline. This study aims to determine the effect of competence and work discipline on employee performance. The population and sample in this study were 52 production employees of CV Budii Jaya. Data collection was carried out by distributing questionnaires which were then processed with the SmartPLS program. The results showed that competence and work discipline had a positive effect on employee performance. The higher the competence of employees, the better the employee performance will be. Likewise with work discipline, the higher the discipline applied by employees, the higher the performance obtained. Keywords: Competence; Work Discipline; Employee Performance